Perspectives and Challenges in Doctoral Research Selected Papers from the 9th Edition of the Scientific Conference of the Doctoral Schools from the "Dunărea de Jos" University of Galaţi - Rusu, Eugen; Rapeanu, Gabriela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes papers from different research fields, reflecting the sectional talks presented at the 9th edition of the Scientific Conference of the Doctoral Schools from the "Dunărea de Jos" University of Galaţi, which took place in June 2021. The objective of the 2021 Conference was to bring together perspectives and challenges in doctoral research in a common forum and to provide a platform enabling doctoral researchers to meet and share state-of-the-art developments in their fields. It consists of 16 papers presented at the 9th edition of the Scientific Conference of the Doctoral Schools from the "Dunărea de Jos" University of Galaţi, in several fields such as: mechanical and industrial engineering, food science and biotechnology, electrical/electronic engineering, systems engineering and information technologies, chemistry, electrochemistry, and economic models and strategies.